Optimal Foot Trajectory Planning of Bipedal Robots Based on a Measure of Falling - Byoung-Ho Kim (International Journal of Advanced Robotic Systems, 2012)
This paper presents a falling-based optimal foot trajectory planning method (FOFTP) for the effective walking of bipedal robots in three-dimensional space. Our primary concern is to determine the optimal footstep location for the more balanced walking of bipedal robots based on a measure of falling. A proper strategy for the intermediate trajectory of the swing foot is also considered. The feasibility of the FOFTP method is verified by a typical bipedal walking simulation. We also discuss the walking efficiency of the proposed approach. It is finally shown that the proposed foot trajectory planning method is applicable for the effective walking of bipeds or humanoid robots.